1993
DOI: 10.1128/aac.37.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin and daptomycin bactericidal activities in the presence of albumin or serum under controlled conditions of pH and ionized calcium

Abstract: Teicoplanin and daptomycin bactericidal rates (BRs) were measured from standard kill curves in supplemented Mueller-Hinton broth (B), B with 3 g of albumin per dl (BA), B with 50%o pooled human serum (BS), and in broth to simulate free concentrations (BF) under controlled physiologic conditions of pH (7.4) and ionized calcium (1.15 to 1.17 mM) against two clinical Staphylococcus aureus strains. Total concentrations of teicoplanin and daptomycin, respectively, were 45 and 12.5 ,ug/ml in B, BA, and BS and 4.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…We have previously reported both decreased killing activity and no effect of the presence of human serum on teicoplanin's bactericidal activity against S. aureus (1,31). The reason(s) for this discrepancy is unclear.…”
Section: In Vitro Model Of Endocarditis a One-compartment In Vitromentioning
confidence: 69%
“…We have previously reported both decreased killing activity and no effect of the presence of human serum on teicoplanin's bactericidal activity against S. aureus (1,31). The reason(s) for this discrepancy is unclear.…”
Section: In Vitro Model Of Endocarditis a One-compartment In Vitromentioning
confidence: 69%
“…Mueller-Hinton broth II (MHB II; Difco, Detroit, MI) with 25 mg/liter of calcium and 12.5 g/ml magnesium was used for susceptibility testing and in vitro pharmacodynamic simulated endocardial vegetation (SEV) models. Due to the dependency of daptomycin on calcium for antimicrobial activity, supplemented MHB II (SMHB II) containing 50 g/ml of calcium was used for susceptibility testing, and that containing 75 g/ml of calcium (50 and 75 SMHB, respectively) was used for in vitro SEV model experiments (due to binding of calcium by albumin) (25). Colony counts were determined using brain heart infusion agar (BHA; Difco, Detroit, MI).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of action differs from that of the glycopeptides, involving the disruption of amino acid transport by the cell membrane and alterations of the cytoplasmic membrane potential (1)(2)(3). The bactericidal activity of daptomycin is concentration dependent and is influenced by pH and ionized calcium concentrations (9). Like teicoplanin, daptomycin is highly protein bound (94%), and its in vitro activity is altered in the presence of serum or albumin.…”
mentioning
confidence: 99%
“…However, clinical trials were suspended when treatment failures were noted in patients with S. aureus endocarditis (Eli Lilly & Co., personal communication). Possible reasons for failure included the high degree of protein binding and the degree of penetration into cardiac vegetations (9). Experimental animal endocarditis studies replicating clinical trial dosages and achievable concentrations demonstrated that slightly higher dosage regimens of daptomycin were as effective as or more effective than vancomycin in reducing vegetative bacterial densities (8).…”
mentioning
confidence: 99%